Acute EBV masquerading as peripheral T-cell lymphoma. (2nd February 2016) - Zhang, Xiao-Yin; Collins, Graham P; Soilleux, Elizabeth; Eyre, Toby Andrew
Abstract : Histological features of Epstein-Barr virus (EBV) can rarely mimic lymphoma. A 25-year-old presented with a spontaneous splenic rupture following a short illness. Histopathology assessment of the splenic and marrow tissue was highly suggestive of peripheral T-cell lymphoma not-otherwise-specified (PTCL-NOS). T-cell receptor (TCR) PCR clonality studies revealed a monoclonal T-cell population expressing for both TCRβ and γ, strongly suggestive of a T-cell clonal disease. EBV IgM was positive and IgG negative. EBV PCR was positive (7.02 ×10 4 /mL). Despite the strong suggestion of PTCL-NOS from histopathology and clonality studies, the decision was made to observe the patient and not start multiagent chemotherapy. The patient remained well, with no signs of PTCL and subsequently seroconverted to IgG+ EBV. We highlight the potential pitfall of acute EBV masquerading as PTCL and show the critical role of the multidisciplinary integration of histopathological, serology, molecular and clinical features to avoid misdiagnosis.